2022
DOI: 10.23937/2474-3682/1510195
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Seborrheic Keratosis of the Umbilicus

Abstract: We report the case of an atypical seborrheic keratosis located at the umbilicus with misleading dermoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…When it comes to seborrheic keratosis, the systematic review revealed a single case that met the inclusion criteria. The dermoscopic image presented by Hamich et al [ 38 ] was not specific and comprised an exophytic keratotic projection pattern with dotted vessels, brown and yellowish structureless areas, and aggregated blue-grey globular-like structures ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to seborrheic keratosis, the systematic review revealed a single case that met the inclusion criteria. The dermoscopic image presented by Hamich et al [ 38 ] was not specific and comprised an exophytic keratotic projection pattern with dotted vessels, brown and yellowish structureless areas, and aggregated blue-grey globular-like structures ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…When it comes to seborrheic keratosis, the systematic review revealed a single case that met the inclusion criteria. The dermoscopic image presented by Hamich et al [38] was not specific and comprised an exophytic keratotic projection pattern with dotted vessels, brown and yellowish structureless areas, and aggregated blue-grey globular-like structures (Figure 7). (B) Dermoscopy shows structures corresponding to both seborrheic keratosis and dermal nevus, namely dark-brown structureless areas, thick curved lines (fissures and crypts), and white/yellow disseminated dots/clods (milia-like cysts) in seborrheic keratosis and a light-brown pigmented network and structureless areas along with dotted vessels and white/yellow disseminated dots/clods (milia-like cysts) in dermal nevus (FotoFinder, Medicam 800 HD, FotoFinder Systems GmbH, Bad Birnbach, Germany; ×20 magnification, immersion gel).…”
Section: Seborrheic Keratosismentioning
confidence: 99%
See 1 more Smart Citation